2018
DOI: 10.1111/jpn.13005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplemental methionine source and betaine replacement on the growth performance and activity of mitochondrial respiratory chain enzymes in normal and heat‐stressed broiler chickens

Abstract: This study aimed to evaluate the effects of dietary supplemental methionine (Met) source and betaine (Bet) replacement for Met on performance and activity of mitochondrial respiratory chain enzymes (MRCEs) in normal and heat‐stressed broiler chickens. Total of 1,200‐day‐old Ross 308 chicks were allocated to two houses, each consisted of 12 treatments, five replicates of 10 birds each with 2 × 2×3 × 2 (temperature × Met source × Met level × Bet, respectively) split‐plot factorial arrangement. Met level in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
1
10
0
4
Order By: Relevance
“…Also, methionine is an essential factor in heat stress resistance. It is a glutathione precursor; it relives reactive oxygen species (ROS); therefore, supplementation of methionine can contribute to the antioxidant status of poultry (Sahebi Ala et al 2019 ). Methionine can be gained through diet; therefore, much or less Met consumption can result in DNA methylation shift (Niculescu and Zeisel 2002 ), which may, in turn, support genomic insecurity (Arai and Kanai 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, methionine is an essential factor in heat stress resistance. It is a glutathione precursor; it relives reactive oxygen species (ROS); therefore, supplementation of methionine can contribute to the antioxidant status of poultry (Sahebi Ala et al 2019 ). Methionine can be gained through diet; therefore, much or less Met consumption can result in DNA methylation shift (Niculescu and Zeisel 2002 ), which may, in turn, support genomic insecurity (Arai and Kanai 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…As core temperature is a key indicator of exercise-associated GI disturbances [ 77 , 78 , 85 , 86 ], if betaine can attenuate the rise in core temperature during exercise in the heat, endotoxemia and thereby heat-related injuries may be preventable. The majority of this work has been performed in animal models (i.e., chickens, cows, ducks, goats, poultry, and sheep) with most demonstrating betaine to effectively combat thermal stress [ 84 , 87 , 88 , 89 ].…”
Section: Animal Models Of Heat Stressmentioning
confidence: 99%
“…Additionally, betaine supplementation may play an indirect role in managing heat stress through alterations in cellular metabolism and blood chemistry. Several researchers have demonstrated that broiler chickens without betaine supplementation experienced a reduction in mitochondrial function when exposed to heat stress [ 87 , 93 ]. However, betaine supplementation successfully attenuated this loss, restoring function to thermoneutral levels [ 87 ].…”
Section: Animal Models Of Heat Stressmentioning
confidence: 99%
See 2 more Smart Citations